A Randomized Controlled Trial of Whole Body Vibration Exposure on Markers of Bone Turnover in Postmenopausal Women. (27th June 2011) - Turner, Sarah; Torode, Margaret; Climstein, Mike; Naughton, Geraldine; Greene, David; Baker, Michael K.; Fiatarone Singh, Maria A.
Abstract : Purpose . To examine the effects of two doses of low-frequency (12 Hz), low-magnitude (0.3 g), whole body vibration on markers of bone formation and resorption in postmenopausal women. Methods . Women were recruited and randomized into a sham vibration control group, one time per week vibration group (1×/week), or three times per week vibration group (3×/week). Vibration exposure consisted of 20 minutes of intermittent vibration for the 1×/week and 3×/week groups, and sham vibration (<0.1 g) for the control group for eight weeks. Double-blinded primary outcome measures were urine markers of bone resorption: N-telopeptide X normalised to creatinine (NTx/Cr) and bone formation: bone-specific alkaline phosphatase (ALP). Results . Forty-six women (59.8 ± 6.2 years, median 7.3 years since menopause) were enrolled. NTx/Cr was significantly reduced (34.6%) in the 3×/wk vibration group but not in the 1×/wk vibration group compared with sham control (P < .01 ) group. No effect of time or group allocation was observed on the bone formation marker ALP (P = .27 ). Conclusion . We have shown for the first time that low-frequency, low-magnitude vibration 3×/week for eight weeks in postmenopausal women results in a significant reduction in NTx/Cr, a marker of bone resorption, when compared with sham vibration exposure.